Anion and pH-regulated assembly of three Cd(II) coordination polymers based on 3, 5-di(1H-benzo[d]imidazol-1-yl)benzoate. Issue 1 (2nd January 2017) - Li, Chao-Jie; Zheng, Sheng-Run; Chen, Zhi-Yuan; Hu, Wei-Dong; Cai, Song-Liang; Fan, Jun; Zhang, Wei-Guang
Abstract: Three coordination polymers, {[CdI(DBBA)]∙0.5H2 O}n (1, DBBA = 3, 5-di(1Hbenzo[d]imidazol-1-yl)benzoate), [Cd(DBBA)(CH3 COO)]n (2 ) and [Cd(DBBA)2 ]n (3 ), were obtained through reactions between Cd(II) salts and 3, 5-di(1H-benzo[d]imidazol-1-yl)benzoic acid under different pH conditions. Compounds1 and2 are 3-D frameworks withrtl topology based on different binuclear Cd(II) secondary building units. Compound3 was formed at lower pH and showed a 1-D chain assembled with M2 L2 ring units. Moreover, phase purities, thermal behaviors, and photoluminescent properties have also been investigated. Abstract :